C Edu-Aksi Holistic Green Business Pada Mahasiswa dalam Upaya Pengurangan Limbah Kosmetik ke Tempat Pembuangan Akhir - Nasywa Mukhbita Nayla; Lina, Angie Angel Lina; Safi'i, Iwan Safi'i; Arkananta, Edgina Rangga Arkananta; Anggraeniko, Litya Surisdani Anggraeniko (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
Cosmetics are beneficial products that serve to protect the body and face while aiming to enhance appearance. Despite their benefits, cosmetic waste that is not properly managed can contribute to environmental pollution. Therefore, it is crucial to understand the environmental impact of cosmetic use and explore ways to reduce production waste. The Holistic Green Edu-Action initiative focuses on reducing cosmetic waste directed to landfills. This project integrates education and concrete actions to raise public awareness, particularly through webinars discussing the role of social media in environmental stewardship. These webinars emphasize how social media platforms can be effectively utilized to educate the public about the dangers of cosmetic waste and encourage community involvement in better waste management practices. The project aspires to create a positive impact on the environment and minimize the amount of cosmetic waste ending up in landfills.